A Hollow‐Core Optical Cavity Built in a Three‐Layer Silicon Photonic Crystal. Issue 10 (19th July 2013) - Wang, Jian; Ouyang, Jing; Varghese, Leo T.; Fan, Li; Xuan, Yi; Qi, Minghao
<x xml:space="preserve">Abstract</x> Hollow‐core (HC) optical microcavities differ from conventional ones in that they can strongly confine light in air. HC cavities simultaneously possessing high air–energy ratios (αair), high quality factors (Q), and small mode volumes (Veff) may enable on‐chip low‐concentration molecular sensing, high optical power delivery or storage, and low‐threshold optical oscillation or lasing when filled with materials of desirable nonlinearities. However, designing and fabricating such cavities has been challenging, especially when using only a small number of layers. Here, the design and fabrication of such an HC cavity in a three‐layer silicon photonic crystal (PhC) is reported. It supports a transverse magnetic (TM) cavity mode with αair ≈ 67% and Q ≈ 1.7 × 105 in the 1550 nm wavelength range. The in‐plane confinement is provided by the 2D photonic bandgap (PBG) of a dielectric rod array, while a pair of capping slabs with air–hole PhC patterns confine light in air in the vertical direction. The cavity allows detection of low‐concentration substances that induce refractive index changes as small as around 8.8 × 10−6. The proposed cavity design and its fabrication provide a new approach to three‐dimensional photonic confinement using a structure consisting of only a few layers.